2010
DOI: 10.15517/rbt.v59i1.3198
|View full text |Cite
|
Sign up to set email alerts
|

Copulatory behaviour and the process of intromission in Anastrepha ludens (Diptera: Tephritidae)

Abstract: Complex genitalia occur in many arthropods and in some species extreme female morphologies lead to serious mechanical difficulties for males. Tephritid flies offer examples of such complex genitalia. Because of their economic importance and the extensive use of sterile male releases for tephritid control in Texas and Mexico, studies have been done on various aspects of their basic reproductive biology, but the process of intromission has received little attention. The distiphallus of the male of Anastrepha lud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…Because the conformation of the endophallic sclerites varies among species, it seems likely that their operation may vary among species as well. For A. ludens, the func tional relationship between the male and female or gans at intromission has been described by Briceno et al (2010). The aedeagus might be described as a long flexible straw (basiphallus) with a leaky balloon (dis tiphallus) attached to the end.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Because the conformation of the endophallic sclerites varies among species, it seems likely that their operation may vary among species as well. For A. ludens, the func tional relationship between the male and female or gans at intromission has been described by Briceno et al (2010). The aedeagus might be described as a long flexible straw (basiphallus) with a leaky balloon (dis tiphallus) attached to the end.…”
Section: Resultsmentioning
confidence: 99%
“…8), dragging the flaccid distiphallus along with it. Briceno et al (2010) found that at insemina tion, the distiphallus was brought into juxtaposition with the openings to the ventral receptacle and sperrnathecae. With these antecedents, we examined July 2014 T h o m a s e t a l .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Males have to accommodate this and move it during copulation without tangling, injury, and breakage. These requirements appear to be problematic, and lacking anatomical specializations and/or mechanisms for accommodation and efficient manipulation of elongated genitalia could represent an impeding factor for the evolution of such genitalia (Briceño et al ., ; Eberhard, ; Gack & Peschke, ; Matsumura & Yoshizawa, , ). This raises the question: how were apparent constraints circumvented several times in insects to allow for the evolution of hyper elongated genitalia?…”
Section: Introductionmentioning
confidence: 99%